The Use of Speech Acts by Native and Non-Native Guests in Ellen Show (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
The aim of the study is to find out the type of illocutionary speech acts that used by native speakers and non-native speakers in Ellen Show. It also analyzes the identifier and the cross-cultural pragmatic background of the speeches. The subjects of the study are BTS as non-native speakers, One Direction and Ellen as native speakers. The study uses qualitative descriptive methods. The result indicated only four types of illocutionary speech acts that found in the videos, representatives, directives, commissive, and expressive. The proposition is dominated by representative’s speech acts with 59.7%, and the second is expressive speech acts with 30.1%. While commissive 5.3% and the last, directives speech acts are 4.9%. The each types of illocutionary speech acts have different identifier. First, expressive speech acts have based of the real situation, giving information, and giving opinion. Second, directives speech acts have direct, request or demand, and suggest or advice. Third, commissive speech acts has expecting future action and promising future action. And the last, expressive speech acts have emotion and attitude. Directives speech acts was not found because Ellen as a host of the show did not change the social status of the guests. Keywords: Illocutionary Speech Acts, Native Speakers, Non-native Speakers, Searle